Cobra Deities and Divine Cobras: The Ambiguous Animality of Nāgas - Lange, Gerrit (Religions, 2019)
In South Asia, cobras are the animals most dangerous to humans—as humans are to cobras. Paradoxically, one threat to cobras is their worship by feeding them milk, which is harmful to them, but religiously prescribed as an act of love and tenderness towards a deity. Across cultural and religious contexts, the Nāgas, mostly cobra-shaped beings, are prominent among Hindu and Buddhist deities. Are they seen as animals? Doing ethnographic fieldwork on a Himalayan female Nāga Goddess, this question has long accompanied me during my participant observation and interviews, and I have found at least as many possible answers as I have had interview partners. In this article, I trace the ambiguous relationship between humans, serpents and serpent deities through the classical Sanskrit literature, Hindu and Buddhist iconographies and the retelling of myths in modern movies, short stories, and fantasy novels. In these narrations and portrayals, Nāgas are often "real" snakes, i.e., members of the animal kingdom—only bigger, shape-shifting or multi-headed and, curiously, thirsty for milk. The article focuses on those traits of Nāgas which set them apart from animals, and on those traits that characterize them as snakes.